The Values outlook of Hui-neng’s Chan Culture and its Realistic Value - Bing-quan, Li (Advances in Social Sciences Research Journal, 2020)
Chan culture created by Hui-neng is one of the three major components of Chinese traditional culture. The value outlook of Chan culture is one of the core values of Chinese traditional culture, which mainly manifests in Equality and Justice, good root, democracy and humanistic feelings, harmony, spiritual freedom and big-hearted. These values of Chan culture are consistent with the cultural psychology and behavior of Chinese nation, and still manifest in the daily life of Chinese people and serve a positive role in the spiritual purification and the promotion of spiritual realm of contemporary people.